Effect of different FRP wrapping arrangements on the confinement mechanism - Pham, Thong; Youssed, J.; Hadi, M.; Tran, T. (Elsevier BV, 2016)
This study aims to investigate the structural behavior and failure modes of fiber-reinforced-polymer (FRP) confined concrete wrapped with different FRP arrangements. A total of twenty four specimens were cast and tested, with three of these specimens acting as reference specimens and the remaining specimens wrapped with different types of FRP (CFRP and GFRP) by different wrapping arrangements. They include fully wrapped, partially wrapped and non-uniformly wrapped concrete cylinders. The non-uniformly wrapped concrete cylinders provided higher compressive strengths and strain for FRP-confined concrete, in comparison with conventional fully wrapping arrangements. The effect of confinement level on the effectiveness of FRP confinement is also investigated. In addition, the partially wrapping arrangements changes the failure modes of the specimens and the angle of the failure surface.